Religious activism in Eastern Europe and beyond. Issue 1 (1st January 2023) - Darieva, Tsypylma; Kormina, Jeanne
ABSTRACT: This collection of contributions addresses the theme of religiously motivated and religiously framed civic activism by bringing together anthropology and theology. The main goal is to put forward a concept of religious activism as local, non-elitist responses challenging dominant discourses and regulation of the religious in authoritarian and more democratic societies. Highlighting complex entanglements of religion, civic engagement, and political participation over the last decade, the authors explore the ways faith-based claims, acts, and initiatives from below are evolving in public spaces, mostly in post-Soviet societies. The contributors to this collection shed light on a variety of faith-based claims arising around religious materiality, governance questions, and unequal access to resources in Russia, Georgia, Eastern Germany, and in the USA. The contributions also identify the means of mediating acts of religious activism, those chosen forms of public expression that make the voices of religious activists more visible and mobilise individual and collective actions in public spaces.